Cognitive performance in late adolescence and long‐term risk of early heart failure in Swedish men. (19th February 2018) - Lindgren, Martin; Eriksson, Peter; Rosengren, Annika; Robertson, Josefina; Schiöler, Linus; Schaufelberger, Maria; Åberg, David; Torén, Kjell; Waern, Margda; Åberg, Maria
Abstract : Aims: Heart failure (HF) incidence appears to increase among younger individuals, raising questions of how risk factors affect the younger population. We investigated the association of cognitive performance in late adolescence with long‐term risk of early HF. Methods and results: We followed a cohort of Swedish men enrolled in mandatory military conscription in 1968–2005 ( n = 1 225 300; mean age 18.3 years) until 2014 for HF hospitalization, using data from the Swedish National Inpatient Registry. Cognitive performance (IQ) was measured through a combination of tests, separately evaluating logical, verbal, visuospatial, and technical abilities. The results were standardized, weighted, and presented as stanines of IQ. The association between IQ and risk of HF was estimated using Cox proportional hazards models. In follow‐up, there were 7633 cases of a first HF hospitalization (mean age at diagnosis 50.1 years). We found an inverse relationship between global IQ and risk of HF hospitalization. Using the highest IQ stanine as reference, the adjusted hazard ratio for the lowest IQ with risk of HF was 3.11 (95% confidence interval 2.60–3.71), corresponding to a hazard ratio of 1.32 (95% CI 1.28–1.35) per standard deviation decrease of IQ. This association proved persistent across predefined categories of HF with respect to pre‐existing or concomitant co‐morbidities; it was less apparent among obese conscripts ( P for interaction =0.0004). Conclusion: In this study of young men, IQ was strongly associated with increased risk of early HF. The medical profession needs to be aware of this finding so as to not defer diagnosis.